Relationship between Writing Arabic Numerals and the Decimal Numerical System among 2nd and 3rd Grade Elementary School Students - Martínez Mora, Brehinert Alfredo; Guerrero López, Diego Fernando (Pensando Psicología, 2013)
The present study aims to explore the relationship between writing Arabic numerals and the decimal numerical system among 2nd and 3rd grade elementary school students. We proposed a quasi-experimental design in which 26 children were asked to perform two operations, transcodification of verbal numbers into Arabic ones and composition using value chips based on verbal expression. The results showed that when children write Arabic numbers incorrectly, they tend to literally write parts of the verbal number. It was also found that, when using the chips, they do not associate the correct system values with the chips of which they consist. The results confirm that, as proposed by Power and Dal Martello (1990), representation that mediates the writing of Arabic numerals is driven by the lexical structure of the verbal expression.
Keywords: arabic numeral verbal expression; asemantic route; semantic route; number transcodification